A study on the use of zinc oxide micro-varistor based field grading materials for composite line insulators - Arabul, Fatma Keskin; Arabul, Ahmet Yigit; Cherney, Edward A.; Jayaram, Shesha H. (IEEE, 2023)
This paper examines the reduction in the electric field at the line end of a 230 kV composite suspension insulator that can be obtained by applying a field grading material (FGM) to the insulator core at the line end of the insulator. The FGM is based on a highly non-linear conductivity zinc oxide micro-varistor material; and COMSOL (R) Multiphysics version 5.6 at power frequency AC is used in the analysis. FGM of various nonlinearities and various lengths applied to the core is studied to determine the non-linear characteristics of the FGM and the length of application that provides the greatest reduction in the electric field. The results are compared to the same insulator fitted with a proper design of corona ring and the simulation results show that the corona ring can be eliminated by using the FGM.
Keywords: polymeric outdoor insulators; field grading materials; finite-element method; e-field; stress-control; corona discharge; Engineering